TYPES OF DIRECTIVE SPEECH ACTS FOUND IN “THE SEA BEAST” MOVIE - Hasra, Sulvira; Nur, Sahril; Fitriyani, Fitriyani (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
Based on this descriptive research, the research formulates two research questions as follows: 1. What directive speech acts are linguistically used by the main character in the "The Sea Beast" movie 2. What are the effects of directive speech acts used by the main character in "The Sea Beast" movie?. The researcher provides an overview related to the data collection and data analysis uses qualitative research. The researcher found 5 types of directive speech acts in accordance with the theory expressed by Yule (1996: 54) asserting that the speaker conveys his wishes. The second research question, researchers found the effects contained in directive speech acts in the movie The Sea Beast. According to the theory outlined by Austin (1962:120), when a speaker influences the listener with their speech, they anticipate a specific action or an impact on the listener's condition. For directive speech acts, 15 extracts were found. There are 3 instances of directive speech acts in the advice category, 3 instances in the command category, 2 instances in the request category, 3 instances in the prohibition category, and finally, 4 instances in the question category. For effect there are two effects of directive speech acts, namely the listener doing and not doing what the speaker wants.